Distinct interferon signatures and cytokine patterns define additional systemic autoinflammatory diseases - de Jesus, Adriana A. (2020)
BACKGROUND. Undifferentiated systemic autoinflammatory diseases (USAIDs) present diagnostic and therapeutic challenges. Chronic interferon (IFN) signaling and cytokine dysregulation may identify diseases with available targeted treatments. METHODS. Sixty-six consecutively referred USAID patients underwent underwent screening for the presence of an interferon signature using a standardized type-I IFN-response-gene score (IRG-S), cytokine profiling, and genetic evaluation by next-generation sequencing. RESULTS. Thirty-six USAID patients (55%) had elevated IRG-S. Neutrophilic panniculitis (40% vs. 0%), basal ganglia calcifications (46% vs. 0%), interstitial lung disease (47% vs. 5%), and myositis (60% vs. 10%) were more prevalent in patients with elevated IRG-S. Moderate IRG-S elevation and highly elevated serum IL-18 distinguished 8 patients with pulmonary alveolar proteinosis (PAP) and recurrent macrophage activation syndrome (MAS). Among patients with panniculitis and progressive cytopenias, 2 patients were compound heterozygous for potentially novel LRBA mutations, 4 patients harbored potentially novel splice variants in IKBKG (which encodes NF-κB essential modulator [NEMO]), and 6 patients had de novo frameshift mutations in SAMD9L. Of additional 12 patients with elevated IRG-S and CANDLE-, SAVI- or Aicardi-Goutières syndrome-like (AGS-like) phenotypes, 5 patients carried mutations in either SAMHD1, TREX1, PSMB8, or PSMG2. Two patients had anti-MDA5 autoantibody-positive juvenile dermatomyositis, and 7 could not be classified. Patients with LRBA, IKBKG, and SAMD9L mutations showed a pattern of IRG elevation that suggests prominent NF-κB activation different from the canonical interferonopathies CANDLE, SAVI, and AGS. CONCLUSIONS. In patients with elevated IRG-S, we identified characteristic clinical features and 3 additional autoinflammatory diseases: IL-18-mediated PAP and recurrent MAS (IL-18PAP-MAS), NEMO deleted exon 5-autoinflammatory syndrome (NEMO-NDAS), and SAMD9L-associated autoinflammatory disease (SAMD9L-SAAD). The IRG-S expands the diagnostic armamentarium in evaluating USAIDs and points to different pathways regulating IRG expression.